Calibrated ages of Port McNeill (PMB) peat core from Canada - Lacourse, Terri (PANGAEA, 2021)
Calibrated ages of a high-resolution peat core from the Past Global Changes - Carbon in Peat on EArth through Time (PAGES_C-PEAT) Project.
Keywords: C-PEAT; Peatland